2021
DOI: 10.1021/acssuschemeng.0c07938
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Assisted Annealing Produces Abundant Macropores in a Carbon Aerogel to Enhance Its Oxygen Reduction Catalytic Activity in Zinc–Air Batteries

Abstract: Carbon aerogels have large specific surface areas suitable for the formation of large numbers of exposed catalytically active sites for oxygen reduction reaction (ORR). In this study, as-prepared carbon aerogels undergo a manganese-assisted annealing process, resulting in a 754 m 2 g −1 specific surface area, abundant macropores, and a fourfold increase in the surface nitrogen content. An optimized Mn−N codoped carbon aerogel, with a 1:10 mass ratio of MnCl 2 •4H 2 O to carbon, annealed at 800 °C, exhibited ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…[19] The high-resolution spectra of Mn 2p (Figure 2b) show distinctive binding energies of Mn 2p 3/2 (640.5 eV) and Mn 2p 1/2 (652.4 eV) as well as an additional satellite peak around 645.3 eV in the GFCs-based materials, which is consistent with the reported Mn 2 + ion in the Mn-N x coordination structure. [20] Additionally, the XPS N1s deconvolution analysis (Figure 2c) show that the GFCs-based materials mainly contain four types of nitrogen configurations including pyridinic N (398.5 eV), Mn-N x species (399.4 eV), graphitic N (401 eV), and oxidized N (403.7 eV). [21] The striking Mn-N x peak proves that metal center atoms are vigorously coordinated with N atoms.…”
Section: Resultsmentioning
confidence: 99%
“…[19] The high-resolution spectra of Mn 2p (Figure 2b) show distinctive binding energies of Mn 2p 3/2 (640.5 eV) and Mn 2p 1/2 (652.4 eV) as well as an additional satellite peak around 645.3 eV in the GFCs-based materials, which is consistent with the reported Mn 2 + ion in the Mn-N x coordination structure. [20] Additionally, the XPS N1s deconvolution analysis (Figure 2c) show that the GFCs-based materials mainly contain four types of nitrogen configurations including pyridinic N (398.5 eV), Mn-N x species (399.4 eV), graphitic N (401 eV), and oxidized N (403.7 eV). [21] The striking Mn-N x peak proves that metal center atoms are vigorously coordinated with N atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The key to the breakthrough of non-noble metal electrocatalysts in ORR is to obtain performance comparable to that of noble metal catalysts [ 68 , 72 ]. Metal particles are easily sintered and aggregated at high temperatures, which is not conducive to the progress of catalytic reactions.…”
Section: Applications Of Cas In Electrocatalysismentioning
confidence: 99%
“…Heterostructural composites can be synthesized by adjusting the reduction potentials of different metal ions in precursors. For example, Co 2+ can be reduced to metallic cobalt particles at 800 °C, , while the more oxidizing Mn 2+ tends to remain at a higher valence at the same temperature. , Keeping this in mind, we can then synthesize a large variety of heterostructural electrocatalysts with diverse metal-based phases, including metals, alloys, and compounds, where the unique structure and composition of each phase collectively contribute to the overall electrocatalytic activity. Previous studies have shown that these heterostructural electrocatalysts possess better ORR activity than those with a single metal-based phase, which is usually generalized as interfacial synergy between multiple phases. In these studies, the so-called interfacial synergy was believed to enhance the electronic conductivity, tune the electronic structure, or cause complex electronic states, ,, but the specific roles played by each phase were rarely discussed and emphasized, which makes the material design in many of these studies somewhat arbitrary.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Co 2+ can be reduced to metallic cobalt particles at 800 °C, 18,19 while the more oxidizing Mn 2+ tends to remain at a higher valence at the same temperature. 20,21 Keeping this in mind, we can then synthesize a large variety of heterostructural electrocatalysts with diverse metal-based phases, including metals, alloys, and compounds, where the unique structure and composition of each phase collectively contribute to the overall electrocatalytic activity. Previous studies have shown that these heterostructural electrocatalysts possess better ORR activity than those with a single metal-based phase, which is usually generalized as interfacial synergy between multiple phases.…”
Section: ■ Introductionmentioning
confidence: 99%